Características de la Morbilidad Materna Extrema en el Hospital Regional de Ayacucho, Perú, 2021-2023 - Rojas, Ramiro (2025)
Extreme maternal morbidity (EMM), according to WHO, is a condition in which awoman nearly almost loses her life due to complications during pregnancy, childbirth,or the postpartum period. This rate is higher in low- and middle-income countries.Although maternal mortality has declined in Peru, the EMM is not fully described,underlining the importance of its analysis to improve maternal health services.Objective: To describe EMM in the Regional Hospital of Ayacucho, Peru, betweenJune 2021 and June 2023, and to analyze key indicators to improve maternal care.Materials and methods: An observational, retrospective, cross-sectional study wasconducted with 100 cases of EMM. Socio-demographic data, obstetric characteristics,pathological history and interventions were assessed using epidemiologicalsurveillance forms and formulas to calculate the EMM, maternal mortality ratio andother metrics. Results: The mean age of the patients was 28 years, mostly cohabitingwomen with secondary education. The most frequent criteria for EMM were severehypoxia (50%) and cardiovascular compromise (39%). HELLP syndrome (30%) andpostpartum hemorrhage (22%) were the most common complications. The EMM was19.4 per 1,000 live births and the maternal mortality ratio was 5.75 per 100 cases ofEMM. Conclusions: The EMM in Ayacucho (2021-2023) reveals severe complicationsmainly in young women with low educational level. It is crucial to implement effectiveprevention and management strategies to reduce its incidence and improve obstetricoutcomes.